Kepercayaan Diri Dan Performa Public Speaking: Studi Psikologi Komunikasi Pada Mahasiswa Pascasarjana Di Uin Palopo, Ump, Uncp, Dan Unanda (Universitas Andi Djemma) Palopo - Wulandari, Wulandari; Hasyim, Baso; P, Efendi (IAIN Padangsidimpuan, 2025)
This study aims to identify the level of self-confidence of postgraduate students in public speaking, describe their public speaking performance in academic and professional forums, and analyze the relationship between self-confidence and public speaking performance within the framework of communication psychology theory. A quantitative, non-experimental correlational approach was employed to examine the extent of the relationship between self-efficacy and public speaking performance. The non-experimental design was chosen because the researcher did not manipulate independent variables or apply specific treatments, but rather observed the natural relationship between them. This study is exploratory-quantitative in explaining the psychological and communicative dynamics of students in academic contexts. The research was conducted at four universities in Palopo offering postgraduate programs: UIN Palopo, Universitas Muhammadiyah Palopo (UMP), Universitas Cokroaminoto Palopo (UNCP), and Universitas Andi Djemma (Unanda). The study lasted 1 month and 3 days, from July to August 2025. The population consisted of 113 active postgraduate students in semester ≥ 2, all of whom were selected as respondents using total sampling. Data were collected through online and offline questionnaires based on Bandura’s self-efficacy theory and the Public Speaking Competence Scale (PSCS) by Schreiber, Paul, and Shibley. Data were analyzed using the Kolmogorov-Smirnov normality test, Pearson correlation, and simple linear regression. Results show a strong positive correlation between self-confidence and public speaking performance (r = 0.628). Regression analysis indicates that self-confidence significantly contributes 39.4% to public speaking performance. Most respondents reported moderate levels of self-confidence but high levels of performance.